KINERJA KEUANGAN BANK MILIK PEMERINTAH (BUMN) VS KINERJA KEUANGAN BANK MILIK SWASTA (BUMS) - Nita Eldiani (PRISMAKOM, 2021)
The difference in financial performance between state-owned banks and state-owned banks will measure the bank's ability to maintain company productivity. Financial performance measured in this study is the Sustainable Growth Rate (SGR), Capital Adequacy Ratio (CAR), Dividend Payout Ratio (DPR) and Profit Margin (PM). The purpose of this study is to analyze differences in financial performance between state-owned banks and state-owned banks. This study uses a comparative study (comparative). The population is Government-Owned Commercial Banks (BUMN) and Privately Owned Commercial Banks (BUMS) registered with the Financial Services Authority (OJK). The population in this study includes banking companies registered with OJK in 2012-2017. Comparison of financial performance between state-owned banks and state-owned banks in this study shows that state-owned banks still have superior financial performance. This can be seen from each ratio being compared, state-owned banks have a higher ratio value than state-owned banks. Even though state-owned banks are superior in financial performance, it is possible for state-owned banks to match or even be better in producing financial performance. This is supported by a fairly competitive business world. Companies/banks that continue to innovate for customer satisfaction will be able to survive and even grow.